2022
DOI: 10.3390/earth3030058
|View full text |Cite
|
Sign up to set email alerts
|

Bush Encroachment and Large Carnivore Predation Success in African Landscapes: A Review

Abstract: Bush encroachment is a habitat change phenomenon that threatens savanna and grassland ecosystems worldwide. In Africa, large carnivores in bush encroached landscapes must adjust to increasing woody plant cover and biomass, which could affect predation success at multiple stages through complex and context-dependent pathways. We highlight, interpret, and compare studies that assessed how bush encroachment or related habitat parameters affect the predation stages of large African carnivores. Bush encroachment ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 113 publications
0
2
0
Order By: Relevance
“…Cheetahs appeared to use habitat for hunting in relatively equal proportions across vegetation classes. Although bush encroachment affects cheetah habitats in many regions (Atkinson et al., 2022a), cheetahs have been shown to hunt successfully in areas affected by woody cover up to a certain threshold (Atkinson et al., 2022b). While prey catchability for a specialised cursorial predator such as the cheetah might be most efficient in open areas, vegetation cover can provide safe refuge from scavengers especially in systems where dominant carnivores that represent a potential threat to cheetahs, such as lion and spotted hyaena are absent (Atkinson et al., 2022a).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cheetahs appeared to use habitat for hunting in relatively equal proportions across vegetation classes. Although bush encroachment affects cheetah habitats in many regions (Atkinson et al., 2022a), cheetahs have been shown to hunt successfully in areas affected by woody cover up to a certain threshold (Atkinson et al., 2022b). While prey catchability for a specialised cursorial predator such as the cheetah might be most efficient in open areas, vegetation cover can provide safe refuge from scavengers especially in systems where dominant carnivores that represent a potential threat to cheetahs, such as lion and spotted hyaena are absent (Atkinson et al., 2022a).…”
Section: Discussionmentioning
confidence: 99%
“…Cheetahs appeared to use habitat for hunting in relatively equal proportions across vegetation classes. Although bush encroachment affects cheetah habitats in many regions (Atkinson et al, 2022a), cheetahs have been shown to hunt successfully in areas affected by woody cover up to a certain threshold (Atkinson et al, 2022b).…”
Section: Habitat Usementioning
confidence: 99%
See 1 more Smart Citation
“…The movements of Rehabilitated Translocated cheetahs in relation to the hard edge between human-managed open savanna and bush encroached woodland savanna revealed a non-linear relationship. Habitat edges are often favoured by prey and also provide concealment, which can assist in hunting (Bissett and Bernard, 2007;Atkinson et al, 2022b).…”
Section: Factors Associated With Movementsmentioning
confidence: 99%
“…The world's primary cheetah population stronghold is in southern Africa (Durant et al, 2017;Marker et al, 2018a), but cheetahs therein are subject to lethal persecution on livestock farms and in many areas must contend with bush encroachment, which can alter both predator and prey behaviours (Marker and Dickman, 2004;Nghikembua et al, 2021;Atkinson et al, 2022a;Nghikembua et al, 2023). Habitat change to woody vegetation potentially affects the cheetah's hunting strategies and energy acquisition, given their preference for open landscapes (Caro, 1994;Atkinson et al, 2022b). While both human-wildlife conflict and habitat change can be tackled with management and education, in some areas the cheetah populations are low or extinct, and restoration requires translocations for population recovery.…”
Section: Introductionmentioning
confidence: 99%